Peningkatan Kedisiplinan Melalui Media Stik Ice Cream Pada Siswa Kelompok B di TK Al Hidayah Jambewangi 01 - Mukaromah, Binti; prawinda, raras ayu; Rachmah, laela Lutfiana; farantika, dessy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Character education is very important to instill in children from an early age. therefore, schools which are places that contribute greatly to the formation of children's attitudes, are obliged to include elements of character education in their students. One of these characters is the character of discipline. Children are not directly involved in learning activities and everyday problem solving. Yet this is very important for the development of children. Therefore, it is necessary to find a solution to this problem by using ice cream stick learning media. The ice cream sticks will be carried out using a reward and punishment system. In addition, giving punishment to children is illustrated by bad things, such as scolding children and punishing children, but the purpose of the teacher or parents giving punishment is so that children become disciplined in the future and do not repeat the mistake he had made. Based on the results of data analysis in the pre-study, a percentage of 44% was obtained, while in cycle I, a percentage of 60% was obtained. In cycle II, the percentage reached 82%, with the acquisition of these data there was a significant increase in children's disciplinary behavior in pre-research to cycle I and from cycle I to cycle II. Based on these data, this research can be said to be successful because in cycle II there was an increase, and it was included in the good category